Students’ Stories of Studying Abroad: Reflections Upon Return - Costello, Jane (Journal of International Students, 2015)
Study abroad brings an enriching experience to students’ academic and personal lives. This narrative essay relays two students’ experiences with study abroad sojourns and touches upon their technology use during their study abroad as recounted in semi-structured interviews. Details of their cultural experiences and reflections thereof as well as the impact these experiences had on their lives are presented. Student participation in study abroad semesters is increasing each year. Understanding previous students’ experience studying abroad, how this impacted their studies and life afterwards can inform decision making of other students considering this option. Additionally, awareness of the technologies used to stay in touch with those at home informs administrative and technical decisions for institutions to consider.